2012
DOI: 10.1039/c2ee21995f
|View full text |Cite
|
Sign up to set email alerts
|

Sorption enhanced steam reforming of ethanol on Ni–CaO–Al2O3 multifunctional catalysts derived from hydrotalcite-like compounds

Abstract: This paper describes the sorption of carbon dioxide for enhanced steam reforming of ethanol to produce hydrogen via Ni-CaO-Al 2 O 3 multifunctional catalysts derived from hydrotalcite-like compounds (HTlcs). The catalysts were characterized by N 2 adsorption-desorption, X-ray powder diffraction (XRD), transmission electron microscopy (TEM), H 2 temperature-programmed reduction (H 2 -TPR) and thermogravimetric analysis (TGA) and tested in sorption enhanced steam reforming of ethanol (SESRE), in which products w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
73
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(78 citation statements)
references
References 64 publications
4
73
0
1
Order By: Relevance
“…Apart from post-combustion CO 2 capture, in-situ carbonate looping has also been investigated as means of process intensification in thermodynamically limited reactions, such as oxygenates reforming [27][28][29][30][31] and water-gas shift reaction [32][33][34][35]. Several theoretical [36,37] and experimental [38][39][40][41][42][43] studies on reforming of different fuels combined with CO 2 capture have shown that the addition of the CO 2 sorbent in the reformer shifts the equilibrium of the global reaction to the products' side, leading to increased H 2 efficiency and a CO 2 stream ready for sequestration in a single step, while operating at lower temperature than the conventional processes.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from post-combustion CO 2 capture, in-situ carbonate looping has also been investigated as means of process intensification in thermodynamically limited reactions, such as oxygenates reforming [27][28][29][30][31] and water-gas shift reaction [32][33][34][35]. Several theoretical [36,37] and experimental [38][39][40][41][42][43] studies on reforming of different fuels combined with CO 2 capture have shown that the addition of the CO 2 sorbent in the reformer shifts the equilibrium of the global reaction to the products' side, leading to increased H 2 efficiency and a CO 2 stream ready for sequestration in a single step, while operating at lower temperature than the conventional processes.…”
Section: Introductionmentioning
confidence: 99%
“…The structure is composed of idealized octahedral [Cr III (N 5 O)] cores linked to the octahedral [Na(N 4 O 2 )] cores by two bridging azide ligands. Magnetic properties and EPR of 1 were also studied.Heteromultinuclear complexes have attracted a great attention in the field of coordination chemistry because of their applications for mimicking the active site of some metalloenzymes [1], preparing multifunctional catalysis [2] and are interesting materials for study on magnetic exchange when they include paramagnetic cores [3]. Mixed-metal aggregates, involving intimate association of Na + ions with transition-metal clusters [4], have recently drawn attention because of their interesting structural and magnetic properties and also because of their contribution towards the understanding of molecular recognition in biological systems [5].…”
mentioning
confidence: 99%
“…This novel technology is normally called sorption-enhanced steam methane reforming (SESMR). Indeed, the concept of sorptionenhanced reaction process has recently also been applied to the steam reforming of ethanol and glycerol [11,12].…”
Section: Introductionmentioning
confidence: 99%